Cultural Innovation in Indonesia as a Development of the Creative Economy - Yaya Firmansyah; Wahyu Rafdinal; Abdul Malik Sayuti; Cahaya Juniarti; Nugroho Hardiyanto (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Culture is a part of life that regulates the norms and habits of society. Culture takes two forms: material culture and non-material culture. Through the Creative Economy Agency, the creative economy has been promoted as one of the new pillars of the Indonesian economy. This study aims to analyze the culture-based creative industry as an option for advancing the creative economy in Indonesia. This study applies the theory of economic development by Joseph Alois Schumpeter to emphasize the creativity of entrepreneurs in using existing production factors to support economic activity. Data was collected from secondary data related to the cultural and creative economy. The results show that the creative industry in Indonesia has emerged as the answer to the creative economy system and has also shown rapid development. Practically, in Indonesia, abundant opportunities exist for a culture-based creative economy, spanning various sectors such as arts and tourism, awaiting innovation by industry actors. Government facilitation and increasing engagement from individuals further support this burgeoning creative landscape, aligning with the Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency’s mission to bolster Indonesia's economy by 2030 through successful synergy between government and industry.